Analysis of the Implementation of the Village Fund Management Policy during the Covid 19 Pandemic in the Tangerang District, Banten Province - Gatot Tri Suryanta; Khasan Effendy; Mansyur Achmad; Sampara Lukman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The problem of distributing Village Fund Direct Cash Assistance during the COVID-19 pandemic in Tangerang Regency was not yet on target because there were still overlapping regulatory rules from the central government and the data collection system for aid recipients had not been transparent, making it difficult for the village government to collect data on Village Fund Cash Direct Aid recipients. The theory used Using the Policy Implementation theory according to Grindle (1980) states: "There are two things that will determine the success of the implementation, namely the content of the policy or the content of the policy includes the following: 1) Interests that influence; 2) Types of benefits produced; 3) The degree of change desired; 4) The position of policy makers; 5) (Who) Implements the program; 6) Resources deployed, Meanwhile the implementation context is as follows: 1) The powers, interests, and strategies of the actors involved; 2) Characteristics of institutions and authorities, 3) Compliance and responsiveness. This study uses a qualitative approach with descriptive methods, namely interviews, documentation and observations with data analysis, namely data reduction (data reduction), data display (data display), and conclusion drawing/verification (drawing conclusions/verification). with triangulation technique to the data obtained. Conclusion Research results and discussion Implementation of Village Fund Management policies during the COVID-19 pandemic in Tanggerang district, Banten Province, focus locations in 3 villages (developed, developing and independent villages) 1. Pagedangan village, Pagedangan sub-district, 2 Bojong village, Cikupa sub-district and 3 Curug Sangereng villages Kelapa Dua district. it has not been running in accordance with the objectives of achieving its policy because in reality it has not been able to reduce the poverty rate in Tanggerang district and related to DTKS data collection from the Ministry of Social Affairs and non-DTKS data that has been carried out has not been transparent, making it difficult to collect data on Village Fund Direct Cash Assistance recipients during the covid 19 pandemic in Tangerang Regency. Researchers found a new model, namely the Village Development and Empowerment Model towards a just, prosperous and prosperous society, namely the KEVI Model which is expected to be a solution to Village Fund Management policy problems during the pandemic and post-covid-19 pandemic in Tangerang Regency, Banten Province.